2007
DOI: 10.1158/1535-7163.mct-06-0358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequently used chemotherapeutic drugs on the cytotoxic activity of human natural killer cells

Abstract: Tumors are considered to be possible targets of immunotherapy using stimulated and expanded autologous or allogeneic natural killer (NK) cells mismatched for MHC class I molecules and inhibitory NK receptors. NK cellbased immunoadjuvant therapies are carried out in combination with standard chemotherapeutic protocols. In the presented study, we characterized the effect of 28 frequently used chemotherapeutic agents on the capacity of NK cells to kill target cells. We found that treatment of NK cells with the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 50 publications
5
81
0
1
Order By: Relevance
“…Furthermore, patients showing a pathologic response tended to show an increased number of infiltrating NK cells compared with poor or nonresponders. While no difference was seen in the number of infiltrating CD56þ NK in a trial of patients with CRC treated with cetuximab compared with noncetuximab-treated patients, tumor-infiltrating CD56þ cells were an independent predictor of PFS and response only in patients treated with cetuximab-based therapies (48). The immune cell infiltration seen with GA201, together with the very significant efficacy difference observed between the glycoengineered GA201 and its wild-type nonglycoengineered version, suggest that the in vivo efficacy of GA201 in such models is likely attributable to the superior immune effector functions of GA201 resulting from an increased binding affinity to FcgRIV and FcgRIIIA on infiltrating mouse monocytes, macrophages and NK cells.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, patients showing a pathologic response tended to show an increased number of infiltrating NK cells compared with poor or nonresponders. While no difference was seen in the number of infiltrating CD56þ NK in a trial of patients with CRC treated with cetuximab compared with noncetuximab-treated patients, tumor-infiltrating CD56þ cells were an independent predictor of PFS and response only in patients treated with cetuximab-based therapies (48). The immune cell infiltration seen with GA201, together with the very significant efficacy difference observed between the glycoengineered GA201 and its wild-type nonglycoengineered version, suggest that the in vivo efficacy of GA201 in such models is likely attributable to the superior immune effector functions of GA201 resulting from an increased binding affinity to FcgRIV and FcgRIIIA on infiltrating mouse monocytes, macrophages and NK cells.…”
Section: Discussionmentioning
confidence: 89%
“…As mentioned above, high doses of Bortezomib have been reported to inhibit NK cell cytotoxicity (12), which could potentially counteract the observed beneficial effects of MIC induction on the hepatoma cells. Therefore, we treated primary NK cells of healthy donors with different concentrations of Bortezomib for 24 hours and examined NK cell cytotoxicity and IFN-g production in response to K562 target cells, which are the classic target cells for studying NK cell functions.…”
Section: Resultsmentioning
confidence: 95%
“…Although these promising reports suggested a potentially selective effect of Bortezomib on hepatoma cells, a recent study described that high concentrations of Bortezomib inhibited natural killer (NK) cell cytotoxicity (12). These observations raise the concern that a potential antitumor effect of Bortezomib in the context of HCC might be annulled by a negative influence on immune effector cells such as NK cells.…”
mentioning
confidence: 99%
“…Indeed, an 11-y follow-up population study of 3625 people $40 y of age demonstrated that the potency of NK cells in peripheral blood to lyse tumor cell targets is inversely associated with cancer risk (48). Further, delayed acquisition of NK cell cytolytic function following cancer therapy may contribute to recurrent disease (49). Perhaps most intriguing is recent evidence that PTEN can be secreted in exosomes and that the exported PTEN retains its lipid phosphatase ability upon entering the recipient cell (50).…”
Section: Discussionmentioning
confidence: 99%